(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2024)
The present study was conducted to demonstrate the effectiveness of the pomegranate peel aqueous extract against Cronobacter sakazakii (C. sakazakii) isolated from different food sample, C. sakazakii was isolated and identified with biochemical tests. On the other hand, active compounds were extracted from pomegranate peel and a concentration of (0.8,1.6,3.2,6.4,12.8,25.6,51.2,100) mg/ml was prepared. The effectiveness of the pomegranate extract was then evaluated against the growth of the isolates under study using Minimum inhibitory concentration method, the results showed a sensitivity of C. sakazakii to all concentrations. The results showed a difference in the inhibitory effect according to the concentration used. The bacteria were more sensitive to the concentration of 100 mg/ml and less sensitive to the concentration of 25 mg/ml by measuring the diameters of the bacterial inhibition zones of the different concentrations of pomegranate peel extract, the largest diameter inhibition was 37 mm at 100 mg/ml, while the 25 mg/ml concentration showed the lowest diameter was 15 mm. The results of the study suggest that pomegranate peel extracts have an inhibitory effect on C. sakazakii and increase this activity by increasing the concentration used.